2004
DOI: 10.1143/jpsj.73.388
|View full text |Cite
|
Sign up to set email alerts
|

Tight-Binding Molecular Dynamics Study on the Structural Change of Amorphous Germanium with the Increase of Density

Abstract: The structures of low-density and high-density amorphous germanium (a-Ge) are studied, by using the order-N non-orthogonal tight-binding molecular dynamics method, where N is the number of atoms. The initial amorphous configuration is taken from the results of a glass-transition simulation performed in a separate work, with N ¼ 512. From this initial configuration, we gradually increase the density of the system. In low-density a-Ge, the short-range order (SRO) is characterized essentially by the four-fold con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The glass transitions in Si and Ge under pressure were also studied in two recent works both experimentally 14,15 and through molecular dynamic simulations. 16 The combination of Raman and XAS spectroscopy measurements permitted us to confirm that 8 GPa marks the onset of a polyamorphic transition in our more homogeneous samples. 17 Moreover,Ref.…”
Section: Introductionmentioning
confidence: 66%
“…The glass transitions in Si and Ge under pressure were also studied in two recent works both experimentally 14,15 and through molecular dynamic simulations. 16 The combination of Raman and XAS spectroscopy measurements permitted us to confirm that 8 GPa marks the onset of a polyamorphic transition in our more homogeneous samples. 17 Moreover,Ref.…”
Section: Introductionmentioning
confidence: 66%
“…A tight-binding (TB) MD study to examine the pressure effect on structural and dynamical properties of a-Ge has also been reported [274]. The calculations were performed based on the order-N nonorthogonal TB framework using the Fermi operator expansion method [275].…”
Section: Amorphous Gementioning
confidence: 99%
“…Both theoretical and experimental studies [21][22][23][24] have provided enough solid evidence for the existence of such a phase transformation from a low-density semiconducting phase to a high density metallic amorphous phase in a-Ge with the application of pressure. In these studies, however, the influence of pressure on the vibrational properties has not been reported.…”
Section: Introductionmentioning
confidence: 99%